Measurement of the differential cross-sections of inclusive, prompt and non-prompt J/psi production in proton-proton collisions at root s=7 TeV - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
The inclusive J/Ψ production cross-section and fraction of J/Ψ mesons produced in B-hadron decays are measured in proton-proton collisions at √s=7 TeV with the ATLAS detector at the LHC, as a function of the transverse momentum and rapidity of the J/Ψ, using 2.3 pb-1 of integrated luminosity. The cross-section is measured from a minimum pT of 1 GeV to a maximum of 70 GeV and for rapidities within |y|<2.4 giving the widest reach of any measurement of J/Ψ production to date. The differential production cross-sections of prompt and non-prompt J/Ψ are separately determined and are compared to Colour Singlet NNLO*, Colour Evaporation Model, and FONLL predictions. © 2011 CERN.